The Effect of Electroacupuncture at the PC6(Naegwan) and TE5 (Oegwan) on the EEG - Jin-Teck Yim; Su-Hyun Kim; Sang-Ryong Lee (Korean Pharmacopuncture Institute, 2003)
Objectives : The aim of this study was to examine the effects of electroacupuncture(EA) at the PC6(Naegwan) and the TE5 (Oegwan) on normal humans using power spectral analysis. Methods : EEG power spectrum exhibit site-specific and state-related differences in specific frequency bands. In this study, power spectrum was used as a measure of complexity. 30 channel EEG study was carried out in 30 subjects (30 males; age=23.7 years). Results : In α(alpha) band, the power values at F7 channels(p<0.05) during the PC6-acupoint treatment were significantly were decreased. In β(beta) band, the power values at Fp1, Fz, TT1, T5, P3, P4, Po1, Po2, O1, Oz, O2 channels(p<0.05) during the non-acupoint treatment and at Fp1, F4, F8 channels(p<0.05) during the TE5-acupoint treatment significantly were increased. In θ(theta) band, the power values at Fp1 channels(p<0.05) during the non-acupoint treatment and at Oz channels(p<0.05) the TE5-acupoint treatment significantly were increased. but, the power values at F7 channels(p<0.05) during the non-acupoint treatment were significantly were decreased. In δ(delta) band, the power values at TCP1, TCP2, CP1, T5 channels(p<0.05) during PC6-acupoint treatment were increased and the power values at F7, TT2 channels(p<0.05) during non-acupoint treatment were increased. but, the power values at the TE5-acupoint treatment significantly was decreased than the before-acupuncture treatment.